1998
DOI: 10.1038/25133
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+/calmodulin signals the completion of docking and triggers a late step of vacuole fusion

Abstract: The basic reaction mechanisms for membrane fusion in the trafficking of intracellular membranes and in exocytosis are probably identical. But in contrast to regulated exocytosis, intracellular fusion reactions are referred to as 'constitutive' as no final Ca2+-dependent triggering step has been observed. Although transport from the endoplasmic reticulum to the Golgi apparatus in the cell depends on Ca2+, as does endosome fusion and assembly of the nuclear envelope, it is unclear whether Ca2+ triggers these eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
402
1
4

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 372 publications
(426 citation statements)
references
References 30 publications
19
402
1
4
Order By: Relevance
“…Ion dysregulation could in turn have indirect consequences on other processes in OCA2-deficient cells. For example, alterations in intralumenal ion balance or pH can affect cellular membrane fusion events (Peters and Mayer, 1998;Ungermann et al, 1999;Pryor et al, 2000), perhaps explaining the accumulation of melanosomal cargo in vesicular structures in OCA2-deficient melanocytes (Manga et al, 2001). Moreover, disruption of OCA2 transport activity across the melanosomal membrane may indirectly alter ion concentrations or pH in the cytosol; for example, exogenous expression of OCA2 in Saccharomyces cerevisiae led to a depletion of cytoplasmic glutathione due to glutathione transport into the vacuole (Staleva et al, 2002).…”
mentioning
confidence: 99%
“…Ion dysregulation could in turn have indirect consequences on other processes in OCA2-deficient cells. For example, alterations in intralumenal ion balance or pH can affect cellular membrane fusion events (Peters and Mayer, 1998;Ungermann et al, 1999;Pryor et al, 2000), perhaps explaining the accumulation of melanosomal cargo in vesicular structures in OCA2-deficient melanocytes (Manga et al, 2001). Moreover, disruption of OCA2 transport activity across the melanosomal membrane may indirectly alter ion concentrations or pH in the cytosol; for example, exogenous expression of OCA2 in Saccharomyces cerevisiae led to a depletion of cytoplasmic glutathione due to glutathione transport into the vacuole (Staleva et al, 2002).…”
mentioning
confidence: 99%
“…A regulatory role for Ca 2+ has been established in many other fusion reactions. For example, it controls the fusion of secretory vesicles and of vacuoles [31]. We do not observe the obvious differences of free Ca 2+ levels in all the three different ratios of cytosol to vesicles (data not shown).…”
Section: Discussionmentioning
confidence: 59%
“…Pharmacological studies indicate that calmodulin is required for late-stage vacuole fusion in vitro and in vivo [31]. A large proportion of the bound calmodulin is released from the vacuole at Ca 2+ concentrations below 500 nM, and the Ca 2+ concentration in the cytosol of living yeast cells is 100-150 nM [32], which is within this range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using an in vitro model for homotypic vacuole fusion in yeast, Peters & Mayer (1998) observed that vesicle fusion was exquisitely sensitive to calmodulin antagonists late in the docking phase and early in the final fusion steps leading to membrane incorporation. Fusion could be blocked at these stages in vivo using temperaturesensitive calmodulin yeast mutants, and the same block in vitro was relieved on adding wild-type calmodulin.…”
Section: Snares and Associatesmentioning
confidence: 99%